Retinal prostheses: progress toward the next generation implants - Ghezzi, Diego (Frontiers in Neuroscience, 2015)
In the last decade, various clinical trials proved the capability of visual prostheses, in particular retinal implants, to restore a useful form of vision. These encouraging results promoted the emerging of several strategies for neuronal stimulation aiming at the restoration of sight. Besides the traditional approach based on electrical stimulation through metal electrodes in the different areas of the visual path (e.g. the visual cortex, the lateral geniculate nucleus, the optic nerve, and the retina), novel concepts for neuronal stimulation have been mostly exploited as building blocks of the next generation of retinal implants. This review is focused on critically discussing recent major advancements in the field of retinal stimulation with particular attention to the findings in the application of novel concepts and materials. Last, the major challenges in the field and their clinical implications will be outlined.